Characterization of Extract of Aeromonas hydrophila - SHEN Jin-yu; YU Xu-ping; Kim Thompson; Alexandra Adams (浙江大学学报. 农业与生命科学版)
Whole cell (WC) and extract from six virulent strains of Aeromonas hydrophila were characterized by SDS-PAGE and Western blot analysis. The protein profiles of WC and extract indicated that all the isolates on different conditions had various bands but had the same molecular weight bands. The same isolate on five conditions had the similar bands pattern. Schiff's reagent, Silver stain and Lectin staining (BS-1, ConA, UEA-1) were used to examine and characterize carbohydrate presented in the extract. The lectin staining and silver stain (proteinase K treated extract) showed all the isolates which produced bands representing carbohydrates of different molecular weights, the 32 kDa band being recognized by three lectins and silver stain, 34 kDa band by lectin BS-1 and UEA-1. The gels were also stained by Schiff's reagent, but only few bands appeared. Tilapia anti-A. hydrophila sera against live and killed T4 were prepared to determine the antigenicity of extract by Western blot analysis. The results indicated that various bands of. extract of A. hydrophila could be recognized by both fish sera. However, the reaction of serum against the live bacteria was stronger than that against the killed. It appeared that all the isolates expressed a 35 kDa band when the extract was performed on any one of the five mediums, which was reacted with fish antibody. This showed that the 35kDa band may be a common antigen in all these 6 bacterial pathogens and suggests that the 35 kDa band may represent a protein. The antibody titer and cross-reaction of fish serum were confirmed by ELISA test.